Financial sector development convergence in Africa: Evidence from bank- and market-based measures - Sare, Yakubu Awudu; Opoku, Eric Evans Osei; Ibrahim, Muazu; Koomson, Isaac (Economics and Business Letters, 2019)
In this paper, we employ data from 46 African countries over the period 1980–2014 to examine financial sector development convergence, using bank- and market-based measures of financial development. Within the framework of the generalized method of moments (GMM), we present evidence that both the bank– and market–based financial sector development in Africa diverge over time. However, we find strong evidence of financial development divergence when using bank-based financial sector development indicators whereas this evidence is weaker for market-based indicators. Given the divergence in the level of finance, the gap between countries with underdeveloped and well–developed financial markets will continue to widen as financially less developed countries do not appear to catch-up with the financially more developed economies. Keywords: Financial development; divergence, convergence, Africa JEL Classification: F15, F36, G01, O55